RELATIONSHIP BETWEEN ACADEMIC RESILIENCE AND ACADEMIC ACHIEVEMENT AMONG SECONDARY SCHOOL STUDENTS IN PHYSICS IN AWKA EDUCATION ZONE, ANAMBRA STATE (UNIZIK Journal of STM Education, 2025)
The study investigated the relationship between academic resilience and academic achievement among secondary school students in Physics in Awka Education Zone of Anambra State. The research was guided by two research questions and two null hypotheses which were tested at 0.05 level of significance. Correlation research design was adopted for the study. The population of the study comprised 2532 secondary school two (SS 2) students offering Physics from 62 public secondary schools in the Zone. Multi-stage sampling procedures was used to draw 345 sample size from the population. The instruments used for data collection included; Physics Resilience Questionnaire (PRQ) and average scores of students for 2024/2025 academic session. The instrument PRQ was validated by three experts, two from the Department of Science Education and one from Educational Foundations (Measurement and Evaluation unit), all in Nnamdi Azikiwe University, Awka. The reliability of the instruments were established using Cronbach's alpha, with coefficients of 0.79 for PRQ, indicating satisfactory internal consistency. The data collected were analyzed with Pearson Product-Moment Correlation and Multiple Linear Regression analysis, using Statistical Package for Social Sciences (SPSS, version 25). The findings of the study showed that there is a weak positive relationship between academic resilience and academic achievement among SS2 students offering Physics. The study further showed a weak positive significant relationship between academic resilience and academic achievement among male students while it showed a moderate positive significant relationship between academic resilience and academic achievement among female students. Based on the findings, the study concluded that students who demonstrate higher levels of academic resilience tend to perform better academically, but the influence of resilience on achievement is relatively low. Furthermore, academic resilience contributes more significantly to the academic achievement of female Physics students than male students. The study recommended amongst others that schools should design interventions such as mentorship, peer-support groups and problem-solving activities that strengthen students’ ability to cope with challenges in Physics learning.
Keywords: Resilience, Academic Achievement, Relationship, Physics, Gender